Systèmes d’instruments des opérateurs. Un point de vue pour analyser le rapport aux règles de sécurité - Christine Vidal-Gomel (Perspectives Interdisciplinaires sur le Travail et la Santé)
Operators develop and use different means to manage professional risks : safety rules, precautionary measures, and informal safety practices. We consider this set of means as an instrument system that operators develop through their professional experience. An occupational accident involving an electrician is analyzed. Our approach allows us to go beyond the framework of safety rules violations and consider all the means that operators develop to manage risks, including their relations, and regard them from a developmental standpoint.